Accelerated/decelerated dynamics of the electric double layer at hydrogen-terminated diamond/Li+ solid electrolyte interface. (February 2023) - Takayanagi, Makoto; Tsuchiya, Takashi; Nishioka, Daiki; Imura, Masataka; Koide, Yasuo; Higuchi, Tohru; Terabe, Kazuya
Abstract: The electrical response of the electric double layer (EDL) effect at the interface between a hydrogen-terminated diamond (H-diamond) and a Li + -conducting solid electrolyte [i.e., LiNbO3 and Li3 PO4 ] was investigated by using an all-solid-state H-diamond-based EDL transistor (EDLT). A 5-nm-thick LiNbO3 or Li3 PO4 interlayer was inserted between a H-diamond and a Li–Si–Zr–O (700 nm) Li + solid electrolyte. We performed Hall measurements and pulse response measurements to investigate the EDL charging characteristics exhibited. The Hall measurements evidenced that all EDLTs exhibited EDL-induced hole density modulation, with a large EDL capacitance ( C EDL ) to 15 μF/cm 2 in the Li  +  -deficient region (negative V G side). On the other hand, in the pulse response measurement, insertion of an LiNbO3 or Li3 PO4 interlayer caused significant acceleration/deceleration of the switching response speed, ranging from τ  = 61.4 ms to 229 μs? C EDL at the LiNbO3 /H-diamond and Li3 PO4 /H-diamond interface, particularly on the Li + rich side, was indicated as determining the switching response speed. The results indicate that the very thin EDL (i.e., 5 Å) can be formed at the solid/solid electrolyte interface, even when inorganic solid electrolytes are used instead of liquid electrolytes, and C EDL at the solid/solid electrolyte can be controlled by electrolyte compositions within a thickness of several Å from the interface. Graphical abstract: Image 1 Highlights: Interlayer caused acceleration and deceleration effects on the EDL charging speed. EDL charging speed was widely tuned in the range of more than 2 orders of magnitude. C EDL was controlled by electrolyte composition within sub-Å thick from the interface. Fast switching less than 230 μs was achieved at RT in all-solid-state EDLTs. V L i ′ - V G curve for Li3 PO4 was steeper than that for LiNbO3 solid electrolytes.